2009
DOI: 10.1021/nl902935b
|View full text |Cite
|
Sign up to set email alerts
|

Protein Nanocapsule Weaved with Enzymatically Degradable Polymeric Network

Abstract: Target proteins can be functionally encapsulated using a cocoon-like polymeric nanocapsule formed by interfacial polymerization. The nanocapsule is cross-linked by peptides that can be proteolyzed by proteases upon which the protein cargo is released. The protease-mediated degradation process can be controlled in a spatiotemporal fashion through modification of the peptide cross-linker with photolabile moieties. We demonstrate the utility of this approach through the cytoplasmic delivery of the apoptosis induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
120
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 140 publications
(120 citation statements)
references
References 37 publications
0
120
0
Order By: Relevance
“…To further enhance biological specificity and therapeutic efficacy, significant efforts have been devoted to explore active targeting 5 and stimuliresponsive DDSs 6 , which specifically accumulate at the tumour site and are stimulated to release drugs within tumour cells. These stimuli can be a variety of external signals, such as temperature 7 , light 8 , magnetic field 9 , ultrasound 10 and electric current 11 , as well as physiological factors, such as pH 12 , redox potential 13 , enzymatic activities 14,15 and glucose levels 16,17 . A number of nanosystems including liposomes 18 , polymeric nanoparticles 19 and inorganic particles 20 have been developed to apply these triggering cues to tailor pharmacokinetics and enhance delivery efficiency.…”
mentioning
confidence: 99%
“…To further enhance biological specificity and therapeutic efficacy, significant efforts have been devoted to explore active targeting 5 and stimuliresponsive DDSs 6 , which specifically accumulate at the tumour site and are stimulated to release drugs within tumour cells. These stimuli can be a variety of external signals, such as temperature 7 , light 8 , magnetic field 9 , ultrasound 10 and electric current 11 , as well as physiological factors, such as pH 12 , redox potential 13 , enzymatic activities 14,15 and glucose levels 16,17 . A number of nanosystems including liposomes 18 , polymeric nanoparticles 19 and inorganic particles 20 have been developed to apply these triggering cues to tailor pharmacokinetics and enhance delivery efficiency.…”
mentioning
confidence: 99%
“…We have previously developed a new strategy for intracellular protein delivery using single-protein nanocapsules (NCs) 110,125 . In this approach, the protein is encapsulated in a thin positively charged polymer shell, which serves as a protective layer.…”
Section: Discussionmentioning
confidence: 99%
“…63 In the current study, we selected a polymeric nanocapsule (NC) strategy for the functional delivery of MBP-APO, in which the protein complex is noncovalently protected in a water soluble polymer shell ( Figure 18). This slightly positively-charged shell shields the MBP-APO from serum proteases and surrounding environment, while enabling cellular uptake of the polymer-protein complex through endocytosis 162 . The polymeric layer is weaved together by redox-responsive cross-linkers containing disulfide bond (S-S) that can be degraded once the NCs are exposed to the reducing environment in cytoplasm 163 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in the field of targeting nanocarriers have shown that the particle size and surface ligand density are critical to their performance (Jiang et al, 2008, Huang et al, 2009, Elias et al, 2013, Bandyopadhyay et al, 2011. Hence, the optimization of these parameters, in combination with PEGylation and targeting moiety density, are crucial to ensure that the functionality of nanocarriers is not compromised.…”
Section: Receptor Mediated Endocytosismentioning
confidence: 99%